2006
DOI: 10.2298/aci0603019p
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic treatment for acute diverticular disease

Abstract: Diverticular disease of the sigmoid colon involves more than 50% of population over 60 years, and much more in people older than 80 years. Most patients remain asymptomatic, but, about 10-20% develop complications requiring surgery. Colonic diverticulitis represents an acute bowel inflammation, in many cases, confined only to the sigmoid and descending colon. Recurrent attacks and complications of diverticulitis require surgical procedure, although most cases can be managed medically. The cause of acute divert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…The methodological evaluation of the non‐RCTs with the MINORS scale showed that two studies scored 21 points (high quality) , two had 17 points and the other two studies scored 10 points (poor quality) (Appendix ). In the non‐RCTs there was a possible selection bias associated with the decision to preserve or to ligate the IMA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The methodological evaluation of the non‐RCTs with the MINORS scale showed that two studies scored 21 points (high quality) , two had 17 points and the other two studies scored 10 points (poor quality) (Appendix ). In the non‐RCTs there was a possible selection bias associated with the decision to preserve or to ligate the IMA.…”
Section: Resultsmentioning
confidence: 99%
“…The electronic search strategy identified 145 citations. After the initial screening of the titles and abstracts and removal of duplications, 58 titles remained, of which 15 were considered relevant [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. A total of eight studies met the inclusion criteria and were included in the analysis [16][17][18][19][20][21][22][23] and seven studies were excluded [24][25][26][27][28][29][30] (see Appendix S1 in the online Supporting Information).…”
Section: Results Of the Searchmentioning
confidence: 99%
See 3 more Smart Citations